Specific leaf area is a potential indicator of tree species sensitive to future climate change in the mixed Subtropical Forests of southern Brazil - Bohora Schlickmann M.* (2020)
© 2020 Elsevier LtdGlobal warming represents one of the most important threats to biodiversity. Because the functional traits of plants influence the performance of individuals under different environmental conditions, we aimed to describe the functional traits of the most frequent tree species found in the Brazilian Mixed Subtropical Forest. We also aimed to test whether functional traits could be used to predict the impact of climate change on the future distribution of tree species. For selected species, certain functional traits were described, namely, wood density, leaf size, specific leaf area, leaf renovation regime, dispersal syndrome, maximum potential height, fruit type, presence of seed dormancy, and the desiccation tolerance of seeds. The geographical distributions of the selected species were modeled using the Maximum Entropy algorithm (MaxEnt) as a function of climatic variation. To predict the impact of climatic changes by 2070 relative to current climate, the best and worst scenarios in relation to the concentration of greenhouse gases (GHG) were used. While the best scenario assumes a strong reduction in GHG anthropogenic emissions, turning negative by 2070, the worst scenario assumes a continuous increase in GHG anthropogenic emissions over time. The functional traits were ordinated by Principal Components Analysis to identify the ecological strategies of each species. The relationship between functional traits and changes to the area of climatic suitability of each species was evaluated using regression trees. Functional traits predicted changes to suitable climatic areas in the worst-case scenario only. The suitable climatic area of more leathery leaf species was predicted to decline by 41.0% on average, whereas that of more membranous leaf species was predicted to decline by 14.0%. In particular, Araucaria angustifolia, which is considered the most representative species of the Mixed Subtropical Forest of Brazil, had the highest sensitivity to climate change. Consequently, our results suggest that this important forest formation will be strongly impacted by climate and will be under severe risk in the future.